Hành vi áp dụng công nghệ 4.0 của doanh nghiệp vùng Đông Nam Bộ, Việt Nam: tác động của bối cảnh công nghệ, tổ chức và môi trường hoạt động - Ngô Hoàng Thảo, Trang; Phạm Khánh, Nam; Trần Thanh, Trúc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
With the rapid development of 4.0 technologies such as the Internet of Things, artificial intelligence, and big data, Vietnamese enterprises are swiftly transforming the use of digital solutions to improve productivity, efficiency, and competitiveness. However, the adoption of technology 4.0 in Vietnam is facing many challenges including issues related to information infrastructure, organization characteristics, and external environment. This study analyzes the current status of 4.0 technology application and factors affecting the decision to apply 4.0 technology to 2,734 enterprises in the Southeast region. The results of the analysis of investment behavior models of enterprises show that only 24,18 percent of enterprises applied 4.0 technologies. The adoption of 4.0 technologies faces several key barriers and challenges, including the institutional environment, the capacity for information technology application, and the skill levels of the workforce in enterprises.